Faktor Dominan Kepatuhan Diet Pada Penderita Diabetes Mellitus Di Wilayah Kerja Puskesmas Tuban - Hidayah, Arinal; Wahyurianto, Yasin; P, Teresia Retna (Peneliti.net, 2024)
One of the diseases that is common suffered by some Indonesian people is diabetes mellitus. The disease is caused by a diet that contains high blood sugar levels and an irregular lifestyle so that people with diabetes mellitus tend to be more severe. This study aims to analyze the dominant factors of dietary compliance of patients with diabetes mellitus in the Tuban health center area. The method used by using the sampling technique is Simple Random Sampling. The variable used is the dominant factor of people with diabetes mellitus. Based on the results of statistical tests, obtained P> (0.005) which means there was no significant relationship between knowledge, motivation and family support for people with diabetes mellitus and dietary adherence. There are 58% for the category of someone who has knowledge, 77% good support from family and 53% personal motivation. So that, maintaining blood sugar levels and obey to a healthy lifestyle is highly recommended for patients to be free from diabetes mellitus and reduce complications in their body.